Adsorption of Some Alephatic Dicarboxylic Acids on Zinc Oxide: A kinetic and Thermodynamic Study (Baghdad Science Journal, 2019)
The adsorption of Malonic acid, Succinic acid, Adipic acid, and Azelaic acid from their aqueous solutions on zinc oxide surface were investigated. The adsorption efficiency was investigated using various factors such as adsorbent amount, contact time, initial concentration, and temperature. Optimum conditions for acids removal from its aqueous solutions were found to be adsorbent dose (0.2 g), equilibrium contact time (40 minutes), initial acids concentration (0.005 M). Variation of temperature as a function of adsorption efficiency showed that increasing the temperature would result in decreasing the adsorption ability. Kinetic modeling by applying the pseudo-second order model can provide a better fit of the data with a greater correlation coefficient, which indicates that the adsorption process follow the pseudo-second order kinetics. The negative values of Gibbs free energy and the enthalpy change confirm the spontaneous and exothermic nature of the adsorption process. A good ability of zinc oxide to remove aliphatic dicarboxylic acids from its aqueous solutions has been found, and the chain length of the acids has no significant effect on its adsorption.